Graphene, related two-dimensional crystals and hybrid systems for printed and wearable electronics. (December 2018) - Torrisi, Felice; Carey, Tian
Graphical abstract: Highlights: We present a comprehensive and updated review of 2D materials for printed and wearable electronics developed with the aim to cover the whole spectrum of research from materials to devices. We introduce the general concepts of printed and wearable electronics, underlining the strong potential for future medical, energy and connectivity applications. We discuss the unique advantaged of graphene and 2D materials enabling high mobility inks for printed electronics and functional thin films and textiles for washable, flexible and skin compatible electronic devices. We propose an updated list of applications of printed and wearable devices in optoelectronics, energy, sensing and integrated circuits. Finally, we envisage a future direction for this field, delivering the full potential of printed and wearable electronics for medical, energy and connectivity areas, fully enabled by 2D materials. Abstract: Graphene, related two-dimensional crystals and hybrid systems showcase several key properties that can address emerging needs in electronics and optoelectronics, in particular for the ever growing markets of printed, flexible and wearable electronic devices. Graphene's flexibility, large surface area, and chemical stability, combined with its excellent electrical and thermal conductivity, make it promising as a printed flexible electrodes in flexible and wearable electronic devices. Chemically functionalized graphene and self-assembly of graphene-organic molecule composites can also improve mobility and conductivity of organic semiconducting thin film transistors (TFT). Two-dimensional crystals and hybrid systems provide optical and electrical properties complementary to those of graphene, enabling the realization of printed an flexible ultrathin-film photodetectors or photovoltaic systems. Here, we review the use of graphene and related materials for printed and wearable electronics and optoelectronics, defining the roadmap for future applications in this area.